NAVIGATING TECHNOLOGICAL DISRUPTION: ETHICAL, LEGAL, ANDSOCIOECONOMIC DIMENSIONS IN CRAFTING A SUSTAINABLE AND JUST TAXATION SYSTEM - Loso Judijanto; Dwi Koerniawati; Shohib Muslim; Pratiwi Subianto; Ahmad Rizani (CV. Adiba Aisha Amira, 2025)
In navigating technological disruption within taxation systems, this research delved into the ethical, legal, and socioeconomic dimensions to craft a sustainable and just framework. Examining past trends and challenges, the study uncovered key findings reflecting stakeholders' heightened awareness, with 8%% expressing concerns about the ethical use of taxpayer data. Though acknowledged by 65% of respondents, the legal landscape faces challenges in adapting to rapid technological advancements, necessitating agile regulatory frameworks. The study revealed nuanced socioeconomic impacts, with 5%% perceiving positive effects on economic growth but 32% expressing concerns about potential disparities. Insights into behavioral aspects indicated a delicate balance, with 6%% recognizing technology's positive influence on compliance behavior, while 45% voiced concerns about its potential misuse. The synthesis of these dimensions underscores the intricate interplay shaping tax technology policies. Acknowledging limitations, including regional variations, the research calls for ongoing exploration into emerging technologies and behavioral dynamics to inform the evolution of ethical and just taxation systems in the digital era.